Style of leadership and organizational culture as moderator of influence of competence and internal control system towards report quality - Putra, I Made Endra Lesmana; Rasmini, Ni Ketut (International Research Journal of Management, IT & Social Sciences, 2018)
The study was intended to obtain an empirical evidence of competence influence of Human Resources and Internal Control System on quality of Local Government Financial Statements (LKPD) with leadership style and organizational culture as moderating variables. There was 39 local structure organization in Denpasar city became a research population. Data were collected through survey method and questionnaire technique. The sample was taken using the non-probability method and purposive sampling technique. There were 152 respondents. Data analysis is used Moderated Regression Analysis (MRA).The result was obtained that the leadership style weakens the influence of human resource competence on LKPD quality in Denpasar. Organizational culture strengthens the influence of human resources competencies in LKPD Denpasar. The leadership style did not moderate the influence of Internal Control System on LKPD quality in Denpasar. Organizational culture strengthens the influence of internal control system on quality in LKPD Denpasar.